2001
DOI: 10.18352/lq.7626
|View full text |Cite
|
Sign up to set email alerts
|

Academic Library Consortia in the United States: An Introduction

Abstract: Library consortia in the United States arose from a need for sharing when resources or funding for those resources were scarce. This is as true today as it was over 100 years ago when the first American consortia were formed. Consortia continue to be a growing and important part of the library profession. This article will give an overview of academic library consortia, with special emphasis on the history and modern developments in the United States and provide a general introduction to the concept of library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…With the advent of the computers in the 1960s, many libraries joined their forces for acquiring expensive library automation systems of that era. This became a model for today's consortia which are formed by the formal agreements of several libraries (Bostick, 2001). With the average number of 186 members, the US library consortiums are the oldest and the largest in the world.…”
Section: Library Consortiamentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of the computers in the 1960s, many libraries joined their forces for acquiring expensive library automation systems of that era. This became a model for today's consortia which are formed by the formal agreements of several libraries (Bostick, 2001). With the average number of 186 members, the US library consortiums are the oldest and the largest in the world.…”
Section: Library Consortiamentioning
confidence: 99%
“…ICOLC is an example of "superconsortium" (Bostick, 2001) and it has several national consortia members as well as regional consortia that have been formed by the consortia from more than one country. One of the regional consortia is SELL which is a consortium from five countries, namely …”
Section: Library Consortiamentioning
confidence: 99%
“…Library consortia have played a critical role in the success of academic libraries, whether this means licensing scholarly resources on behalf of their communities or the non-economic benefits of collaborative activity (Bostick, 2001;Westmoreland & Shirley, 2004) One key reason for joining a library consortium is to obtain economies of scale (Horton & Pronevitz, 2015). The past fifteen years or so has seen a meteoric rise in the collective licensing and acquisition of journals, typically via large "big deal" packages.…”
Section: Library Consortia Engagement With Apcsmentioning
confidence: 99%
“…Potter (1997) stated that library consortium gets established because members benefited with combined set of resources that is greater than the resource of any single member. Bostick (2001) opined that "basic advantage of consortia is sharing resources but it also includes sharing of services, or process such as joint cataloguing of materials or staff and user training, etc". Bostick (2001) reported that sharing with others, who in turn, shared back, meant certain items need not be purchased by every library, collective buying power yields good discount, sharing of services, sharing of staff and training, etc.…”
Section: Library Consortiamentioning
confidence: 99%